Leukocyte telomere length and lung function: a mendelian randomization study in European population - Zhu, Shenyu; Zheng, Wenlong; Rao, Dingyu; Tang, Zhixian; Liao, Xinhui (Frontiers in Physiology, 2024)
Background The telomere has long been regarded as a dependable biomarker for cellular senescence. The lung function can reflect the function and status of the lungs. As individuals age beyond adulthood, there is a gradual decline in lung function. However, the existence of a associated between leukocyte telomere length (LTL) and lung function remains uncertain. Methods A two-sample Mendelian randomization (MR) analysis was used. The Single-nucleotide polymorphisms (SNPs) of LTL from the genome-wide association (GWAS) study were used as exposure instruments variable, and the lung function indicator including Forced expiratory volume in 1-s (FEV1), FEV1 Best measure, FEV1 predicted and Forced vital capacity (FVC) from the Neale Lab and MRC-IEU were used as outcomes. The associated between the exposures and outcomes was assessed using inverse-variance weighted (IVW), MR-Egger, and weighted median methods. Sensitivity analysis was conducted using Cochran’s Q-test, MR-Egger intercept test, MR-PRESSO, leave-one-out analysis, and Steriger test. Results Using the IVW method, a significant association was identified between genetically determined telomere length extension and enhanced lung function in FEV1, with ukb-a-336 (P = 0.127, OR = 1.028,95CI% = 1.003–1.042) and ukb-b-19657 (P = 7.26E-05, OR = 1.051,95CI% = 1.025–1.077),in FEV1 predicted, ukb-a-234 (P = 0.013, OR = 1.029,95CI% = 1.003–1.042), ukb-b-8428 (P = 0.001, OR = 1.032,95CI% = 1.012–1.052), in FEV1 best measure, ukb-a-231 (P = 7.24E-05, OR = 1.050,95CI% = 1.025–1.075), ukb-b-11141 (P = 1.40E-09, OR = 1.067,95CI% = 1.045–1.090).The sensitivity analysis did not reveal heterogeneity or horizontal pleiotropy.Meanwhile, the Steriger test results also indicate that the directionality between exposure and outcome is correct. Therefore, the results indicated robustness. Conclusion There is a correlation between longer LTL and better lung function in the European dataset.